2017
DOI: 10.1063/1.4991381
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and reaction pathways of water near fully hydrated TiO2 surfaces from ab initio molecular dynamics

Abstract: Ab initio molecular dynamics simulations are reported for water-embedded TiO2 surfaces to determine the diffusive and reactive behavior at full hydration. A three-domain model is developed for six surfaces [rutile (110), (100), and (001), and anatase (101), (100), and (001)] which describes waters as “hard” (irreversibly bound to the surface), “soft” (with reduced mobility but orientation freedom near the surface), or “bulk.” The model explains previous experimental data and provides a detailed picture of wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

5
3

Authors

Journals

citations
Cited by 69 publications
(112 citation statements)
references
References 125 publications
6
106
0
Order By: Relevance
“…These results are consistent with the previous reports that molecular adsorption is more energetically favorable on the perfect anatase TiO 2 (101) surface. Water dissociation only occurs on the defective surfaces …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with the previous reports that molecular adsorption is more energetically favorable on the perfect anatase TiO 2 (101) surface. Water dissociation only occurs on the defective surfaces …”
Section: Resultsmentioning
confidence: 99%
“…[16,17] On the other hand, first principle-based density functional theory (DFT) calculations and ab initio molecular dynamics (AIMD) simulations have the advantage of providing detailed structural properties and oxidation states at atomic scales, making them powerful tools in the study of the solid-liquid interfacial chemistry and processes. [18][19][20][21] Results from DFT calculations and AIMD simulations showed that the presence of bulk water has been shown to enhance the stability of the reactant, transition, and product states differently due to the solvation effect, thus affecting the reaction through both thermodynamics (reaction energy) and kinetics (activation barrier). [16,17,[22][23][24][25] To understand the reaction in the aqueous phase, both implicit and explicit H 2 O models have been adopted in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Lipids are described by the Slipids force field 51 . For TiO2, we use parameters optimized to fit results on charge density distributions and water-TiO2 surface coordination obtained in ab-initio simulations of TiO2-water interface 52 . These parameters are listed in tables in SI section S2e.…”
Section: Models Usedmentioning
confidence: 99%
“…The force fields used for describing T iO 2 -adsorbates interactions are normally parametrized for neutral small inorganic molecules, discarding polarization effects due to the strong charge localization at the surfaces, such protonation states. Further the water density profiles at the T iO 2 interface calculated in the DFT [21] and CMD frameworks differ significantly, providing either an overstructured water region [19] that completely hinders the direct molecule adhesion, or a too soft barrier that always allows the direct interaction adsorbate-surface [16][17][18]. Such controversial description of the adsorption mechanism, that lacks a validation against experimental set ups, can be only resolved by first principle calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Atten-tive evaluations of the adsorption free energies were computed to assess the adsorption hierarchy of amino acids interacting with different T iO 2 surfaces [16][17][18][19] or amorphous nanoparticles [20]. The general outcome of this studies strongly relies on the possibility for the amino acids to directly adsorb on the T iO 2 surface, penetrating the strong adsorbed layers of water molecules [21]. The force fields used for describing T iO 2 -adsorbates interactions are normally parametrized for neutral small inorganic molecules, discarding polarization effects due to the strong charge localization at the surfaces, such protonation states.…”
Section: Introductionmentioning
confidence: 99%